2002
DOI: 10.1046/j.1523-1755.2002.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent hemodialysis vascular access survival in children and adolescents with end-stage renal disease

Abstract: Both AVF and AVG function well even in small pediatric patients and have survival rates equivalent to adult series and longer than cuffed venous catheters in pediatric patients. Both AVFs and AVGs are preferable for long-term HD access in pediatrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 16 publications
7
69
1
3
Order By: Relevance
“…This rate has ranged from 10%, reported by Sanabia et al in Spain, in 1993, 35 with microsurgical techniques for AVF construction, to 33%, reported by Sheth et al, in the USA, in 2002. 2 The latter figure is closer to our observation of 37.8% primary AVF failures. Literature results suggest that primary failure correlates more with the surgeon`s expertise, surgical technique and vessel integrity than with vein caliber or patient`s size or age.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This rate has ranged from 10%, reported by Sanabia et al in Spain, in 1993, 35 with microsurgical techniques for AVF construction, to 33%, reported by Sheth et al, in the USA, in 2002. 2 The latter figure is closer to our observation of 37.8% primary AVF failures. Literature results suggest that primary failure correlates more with the surgeon`s expertise, surgical technique and vessel integrity than with vein caliber or patient`s size or age.…”
Section: Discussionsupporting
confidence: 75%
“…Literature results suggest that primary failure correlates more with the surgeon`s expertise, surgical technique and vessel integrity than with vein caliber or patient`s size or age. 2 In order to minimize the technical problems which jeopardize the success of vascular accesses, especially AVF and prostheses, some dialysis centers included in our study have more recently hired experienced vascular surgeons to construct the accesses. Prischl et al 37 have shown that the surgeon`s experience was the main determinant of AVF patency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of adults has shown that HD with any type of venous catheter compared with a graft or fistula increases the risk of both all-cause-related mortality and infection-related mortality [22]. Even in small children, the use of fistulae or grafts is associated with access survival rates equivalent to those of adults and with better survival rates than with cuffed venous catheters [23]. In a 20-year retrospective review of 304 vascular access procedures in children, the median survival time of arteriovenous fistulae was 3.1 years compared to 0.6 years for central venous access [24].…”
Section: Vascular Accessmentioning
confidence: 99%
“…The average survival of CVADs used for hemodialysis is reported to be , 1 year, 643 whereas arteriovenous fi stulas may have as much as a 59% 5-year survival. 645 In a small historical cohort study of children with arteriovenous fi stulas, primary prophylaxis with LMWH was more effective than aspirin, which in turn was more effective at preventing thrombosis than no treatment. 646 Recommendations 2.45.…”
Section: 45-246 Primary Prophylaxis For Venous Access Related To Hmentioning
confidence: 99%